2003
DOI: 10.1189/jlb.0503224
|View full text |Cite
|
Sign up to set email alerts
|

The Src kinase Lyn is a negative regulator of mast cell proliferation

Abstract: Previous investigators have reported that deletion of the protein tyrosine kinase Lyn alters mast cell (MC) signaling responses but does not affect or reduces the cytokine-mediated proliferation of mouse bone marrow-derived MC (BMMC) precursors and of mature MC. We observed that Lyn-deficient mice have more peritoneal MC than wild-type (WT) mice. Studies to explore this unexpected result showed that Lyn(-/-) BM cells expand faster than WT cells in response to interleukin (IL)-3 and stem-cell factor over the 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 21 publications
2
50
0
Order By: Relevance
“…Previous studies using Lyn-deficient mice have shown Lyn to play an essential role in maintaining signaling thresholds in B cells [21,25,26], myeloid cells, including in mast cells [14,19,[34][35][36][37]. Loss of Lyn results in reduced activation of phosphatases, such as SHIP, which results in hypersensitivity to cytokines [19,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using Lyn-deficient mice have shown Lyn to play an essential role in maintaining signaling thresholds in B cells [21,25,26], myeloid cells, including in mast cells [14,19,[34][35][36][37]. Loss of Lyn results in reduced activation of phosphatases, such as SHIP, which results in hypersensitivity to cytokines [19,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of molecules that are activated in response to hematopoietic growth factors include, but are not limited to, nonreceptor tyrosine kinases, such as Src family kinases (SFKs). SFKs function in signal transduction from growth factor receptors for granulocyte macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-3, IL-5, stem cell factor (SCF), erythropoietin, M-CSF, G-CSF, thrombopoietin, and Flt3 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Although diverse cytokine receptors activate SFKs in response to ligand binding, most of the data thus far has been derived by studying cell-line models using dominant negative and activating approaches.…”
mentioning
confidence: 99%
“…In some circumstances, Lyn positively impacts B-cell receptor (BCR) and CD40 signaling (16,17), yet Lyn Ϫ/Ϫ B cells are overactive in response to BCR triggering (18,19). In addition, Lyn Ϫ/Ϫ mast cells hyperproliferate in response to growth factors (20,21). Importantly, Lyn deficiency enhances granulocyte-macrophagecolony stimulating factor (GM-CSF) and M-CSF sensitivity of macrophages (15,22).…”
mentioning
confidence: 99%
“…B cells from Lyn -/-mice were found to be hyper-responsive to BCR engagement (Chan et al, 1997;Hibbs et al, 2002), and to IL-4 stimulation (Janas et al, 1999). Lyn -/-mast cells were also more responsive to proliferative signals delivered by IL-3 or Stem Cell Factor (Hernandez-Hansen et al, 2004). Importantly, Lyn -/-mast cells were more responsive to FcεRI-dependent activation signals (Nishizumi and Yamamoto, 1997;Kawakami et al, 2000).…”
Section: Lynmentioning
confidence: 99%